Pressures in implementation of circular supply chain management for sustainability: An analysis from Indian industries perspective. Issue 5 (25th February 2020) - Saroha, Manju; Garg, Dixit; Luthra, Sunil
Abstract : Purpose: Business organisations are under serious threat to sustain their business due to globalisation, challenging market and recent economic competitiveness. The aim of this study is to address various pressures to circular supply chain management (CSCM) implementation for sustainability. Design/methodology/approach: The present study is based on two research levels. Initially, extensive literature review has been made to identify 31 pressures to CSCM, and eight categories of pressures have been identified. At the second level, fuzzy analytical hierarchy process (F-AHP) has been applied to rank the identified pressures to CSCM implementation for sustainability. Findings: "Financial Pressures (FP)" has been identified as most significant pressure to CSCM implementation for sustainability. Further, "Lack of support of top management (MP1)", "Lack of implementation of laws and policies (GP2)" and "Lack of vision for CSCM (GP1)" have been found most critical sub-pressures CSCM implementation for sustainability. Research limitations/implications: The final results give the prioritised list of all identified 31 sub-pressures and eight main pressure heads, which will be helpful in their removal for achieving the goal of CSCM implementation. It will be helpful for managers to take decisions promoting circular practices in supply chains to achieve truly sustainable supply chains. It will also be help for SC managers to understand the flow of activities and materials in CSC to get good results and remove pressures. Originality/value: The present study plays an important role in circular activities implementation in supply chain for profit gain, and their pressure ranking may help the mangers to implement the CSCM effectively.